Hypertension is prevalent in non-alcoholic fatty liver disease and increases all-cause and cardiovascular mortality - Ng, Cheng Han; Wong, Zhen Yu; Chew, Nicholas W. S.; Chan, Kai En; Xiao, Jieling; Sayed, Nilofer; Lim, Wen Hui; Tan, Darren Jun Hao; Loke, Ryan Wai Keong; Tay, Phoebe Wen Lin; Yong, Jie Ning; Kong, Gywneth; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background & Aims: Hypertension (HTN) is a common comorbidity in non-alcoholic fatty liver disease (NAFLD) affecting up to 40% of individuals. Yet, the impact of HTN and its control, on outcomes in NAFLD remains unclear. Therefore, we aimed to examine the impact of HTN on survival outcomes in a longitudinal cohort of NAFLD patients. Methods: The analysis consisted of adults in the National Health and Nutrition Examination Survey (NHANES) from 1999-2018 with data on socio-demographic characteristics and comorbidities. NAFLD was diagnosed with fatty liver index (FLI) and United States-FLI at a cut-off of 60 and 30 respectively in the substantial absence of alcohol use. Multivariate regression analysis was conducted to adjust for confounders. Results: 45,302 adults were included and 27.83% were identified to have NAFLD. Overall, 45.65% and 35.12% of NAFLD patients had HTN and uncontrolled HTN respectively. Hypertensive NAFLD had an increased risk of all-cause mortality (HR: 1.25, CI: 1.16 to 1.32, p<0.01) and cardiovascular disease (CVD) mortality (SHR: 1.58, CI: 1.17 to 2.11, p<0.01). Well controlled HTN had no significant increased risk of all-cause mortality (HR: 1.20, CI: 0.97 to 1.47, p=0.09) and CVD mortality (SHR: 1.38, CI: 0.86 to 2.20, p=0.19). Conclusion: Despite the significant burden of HTN in NAFLD, up to a fifth of patients have adequate control and the lack thereof significantly increases the mortality risk. With the significant association of HTN in NAFLD, NAFLD patients should be managed with a multidisciplinary team to improve longitudinal outcomes.